International themes in business law - Hardy, Stephen T.; Butler, Mark (Lawyer); Sage eBooks (London : SAGE, 2007)
Including contributions from the main stakeholders in the field this four volume collection of classic and contemporary articles maps out key issues in business law.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Commercial law; Electronic books